2011
DOI: 10.1021/ef1013538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Saline Aqueous Solutions and pH on the Desorption of Crude Oil Fractions from Silica Surfaces

Abstract: Desorption of interfacially active crude oil components was studied by exposing coated silica surfaces to aqueous solutions with different composition. The measurements were carried out for two North Sea crude oils as well as for fractions where the acidic and basic components were removed, respectively. One crude oil was acidic in nature, while the other was basic. Initially, the amount of adsorption onto the silica crystals was determined by a quartz crystal microbalance (QCM). Contact angle measurements sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 48 publications
5
34
0
Order By: Relevance
“…The EDL expansion could also be not large enough to stimulate the attraction of polar components toward the interface to form the viscoelastic interface. The previous study suggested that a critical expansion of the EDL is required for oil displacement [63]. These results also substantiate previous macroscopic core flooding experiments discussed in the literature that the low-salinity effect on EOR from sandstone (silica) is mostly dominated by the presence of significant clay minerals [64].…”
Section: Figure 8 Proposed Chemical Interactions Between Oil/brine/hsupporting
confidence: 90%
“…The EDL expansion could also be not large enough to stimulate the attraction of polar components toward the interface to form the viscoelastic interface. The previous study suggested that a critical expansion of the EDL is required for oil displacement [63]. These results also substantiate previous macroscopic core flooding experiments discussed in the literature that the low-salinity effect on EOR from sandstone (silica) is mostly dominated by the presence of significant clay minerals [64].…”
Section: Figure 8 Proposed Chemical Interactions Between Oil/brine/hsupporting
confidence: 90%
“…In this case, despite the ionic strength of salt solution being reduced at neutral pH value, the repulsive electrostatic force is likely to be insufficient to promote the desorption. Farooq et al [15] found that a critical expansion of the EDL is required for further desorption from silica by low salinity solution.…”
Section: Desorption Of Crude Oil From Calcite and Silica Surfacesmentioning
confidence: 99%
“…The extent of adsorption, desorption, and wettability alteration would depend on both the crude oil properties and the type of EOR fluid. 27 , 28 Notably, in displacement studies using model oils, these phenomena are not an issue.…”
Section: Introductionmentioning
confidence: 99%